Economics and System Theory: Interdisciplinary Connections (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The interdisciplinary interaction between system theory and economics is one of the most promising areas of research. Theoretization associated with economic systems refers to the understanding of economic processes and phenomena in their totality. Research related to economic systems is characterized by integrity and comprehensiveness, as a system in general is larger than its individual elements or structures. Modern scholars investigate various types of economic systems: the global system, national systems and even systems of some enterprises. Since complexity is the characteristic of most economic systems, it is important to draw attention to interdisciplinary links between economics and other sciences. This approach will reveal the essential features of the functioning of economic systems in order to improve their management and governance. To understand economic systems, it is important to develop a theoretical approach that will help to model and predict economic system. Since the economic system is complex, such sciences as law, political science, public administration, sociology, psychology are also included in its consideration. We want to emphasize that the consideration of purely economic issues is one-sided approach to a super-complex phenomenon. That is why, in comparison with economic imperialism, there are other directions concerning alternative ways of organization of economic activity. Thus, an interdisciplinary view of an economic system will increase the efficiency and effectiveness of its understanding. Economy as a system is tightly linked to other systems: legal system, political system, social system, and so on. Given that economic system is not a closed system, numerous connections with other systems are important and interdisciplinary theory is the most productive tool in the study of such relationships. Since scientists and university staff have the necessary knowledge to understand economic systems, we believe that university is the most desirable place to analyze economy as a system characterized by interdependence with other systems.
Keywords: economics, system theory, economic system, socio-economic system, interdisciplinarity.